Cigarette smoking and its impact on fracture healing. (January 2014) - Bender, Daniel; Jefferson-Keil, Tamara; Biglari, Bahram; Swing, Tyler; Schmidmaier, Gerhard; Moghaddam, Arash
In this review, we discuss current knowledge and studies concerning the pathophysiology of cigarette smoking and its impact on fracture healing. We include studies on the biology of fracture healing and more specifically how smoking affects oxygenation in tissues, serum concentrations of important growth factors, collagen synthesis, and bone mineralization. Also mentioned are clinical studies showing that smoking impacts soft tissue regeneration and the healing of tibial fractures and open fractures, as well as articles discussing the apparent benefits and limitations of presurgical smoking cessation. Our review of the current literature suggests that it is necessary to inform smokers with fractures about their increased risk for impaired fracture healing. They should be closely monitored and additional therapies such as the use of BMP-7, BMP-2, or low-intensity ultrasound should be considered in early stages after trauma.